Regulating film, regulating emotion: the emotional history of public opinion. Issue 4 (7th August 2016) - Petersen, Jennifer
ABSTRACT: The article argues that the legal about face in 1950s law in which film was granted First Amendment protection was driven in part by a change in the "emotional regimes" of US democracy, or emotions/performances of emotion that are part of legitimate political culture. The legal understanding of how film does or does not contribute to democratic political culture tracks historical shifts in these emotional regimes. In the teens, elites feared the activation of the masses, as crowds, in political uprisings. By 1950, elite fears had turned to passive audiences, "narcotized" masses that might easily be seduced by totalitarian demagogues.